Karakteristik Plastik Biodegradable Berbasis Onggok dan Kitosan Dengan Plastisizer Gliserol The Characteristics of Biodegradable Plastic Based on Onngok and Chitosan with Plastisizer Glyserol - Devi - Nurlita; Wikanastri - Hersoelistyorini; Muhammad - Yusuf (Universitas Muhammadiyah Semarang, 2017)
Plastic is the one of the most popular packaging in society which in the development kinds of sintetic plastic is made from crude oil and it could not to degradated by microorganism, although had buried for a million time and it caused the environmental pollution. The resolved about that issues, it needed a made film plastic by organic materials, in order to easier degradated such as onggok, chitosan and glycerol as plastisizer. The general objectives of this research is to determine tensile strength, water uptake, and biodegradability of film plastic. This research used completely randomized design (CRD) monofactorial with ratio of onggok and chitosan (b/b) 10:0; 9:1; 8,5:1,5; 8:2; 7,5:2,5; and 7:3. The tensile strength and water uptake data were analyzed statistically using ANOVA and followed by a further test of HSD. In other hand, the biodegradability data is processed with Ms. Excel. The statistical result showed that added by chitosan had effect on water uptake was (p < 0.05). This result same with biodegradability of film plastic that added by chitosan, it can increased biodegradation of film plastic. The statistical result showed that added by chitosan had not effect on tensile strength. The best result of this research was ratio of onggok-chitosan (b/b) 7:3 with 1,045 MPatensile strength number, 53,7 % water uptake, and 5,85 mg/day for biodegradability. The conclusion of this research there were effect of adding chitosan had effect on water uptake and biodegradability of this film plastic is produced.Key words : onggok, chitosan, tensile strength, water uptake, and biodegradable plastic